The lost and found - Teague, Mark. (New York : Scholastic Press, 1998)
When their math teacher sends them to see the principal, two boys risk further punishment by following a new girl who has disappeared into the lost and found bin looking for her lucky hat.
Five Owls.
Publisher's Weekly.
Booklist.
4.2
K-3
Keywords: Lost and found possessions -- Fiction; Schools -- Fiction; Lost and found possessions -- Fiction; School stories; Lost and found possessions -- Fiction; Schools -- Fiction